Analisis Pengungkapan Sustainabilty Report Berdasarkan Standar GRI 400 Pada Sektor Properti - Rafil Rafil; Muhammad Ridho; Kornella Kitty Sitanggang (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze sustainability report disclosures based on the GRI 400 standards in property sector companies listed on the Indonesia Stock Exchange. The study used content analysis of sustainability reports for the 2024 period. Disclosure levels were measured using the GRI 400 disclosure index, which covers 36 social aspect indicators. The results show that property sector companies, on average, disclose only 28% of the GRI 400 indicators. A minimum value of 0 indicates that some companies do not disclose social aspects at all, while a maximum value of 0.75 indicates that no company has fully disclosed all GRI 400 indicators. Furthermore, a standard deviation value of 0.26 indicates significant variation in disclosure across companies. These findings indicate that social aspect disclosure practices in property sector companies' sustainability reports are still uneven and incomplete. Increased corporate commitment and a strengthened role of regulators are needed to encourage sustainability reporting in accordance with Global Reporting Initiative standards.